In vitro remineralization of primary teeth with a mineralization-promoting peptide containing dental varnish (Journal of Applied Oral Science, 2021)
Mineralization-promoting peptides are attractive candidates for new remineralization systems. In previous studies, peptides have been applied as aqueous solutions, which is not a clinically relevant form. Objective: This study aims to investigate the efficiency of a mineralization-promoting peptide, applied in varnish, on remineralizing artificial caries on primary teeth. Methodology: 55 primary molars were collected. Specimens were immersed in a demineralizing solution for 7 days and then, divided into 7 groups: Baseline: No-remineralization, Placebo: Blank colophony, F: Colophony 5% fluoride, P: Colophony 10% peptide, P+F: Colophony 5% fluoride and 10% peptide, Embrace: Embrace™ varnish, Durashield: Durashield™ varnish. A mixture of 35% w/v colophony varnishes were prepared in ethanol and applied accordingly. Specimens were immersed in a remineralization solution for 4 weeks and it was evaluated using PLM and SEM. Lesion depth reduction was examined by one-way ANOVA. Results: There was no significant difference in mean lesion depths between baseline (147.04±10.18 µm) and placebo groups (139.73±14.92 µm), between F (120.95±12.23 µm) and Durashield (113.47±14.36 µm) groups and between P (81.79±23.15 µm) and Embrace (90.26±17.72 µm) groups. Lesion depth for the P+F group (66.95±10.59 µm) was significantly higher compared to all other groups. All groups contained samples with subsurface demineralized regions. Number of subsurface demineralized regions were higher in fluoride-containing groups. Conclusions: We conclude that the mineralization-promoting peptide (MPP3) is effective in this in vitro study and the peptide shows benefits over fluoride as it yields less subsurface demineralized regions.